The Women's Equality Party: Sustainability, Longevity, and Impacts - Vickers, Lisa Marie (University of Cambridge, 2022)
This thesis investigates how the Women’s Equality Party (WEP) in the United Kingdom has struggled to utilise its standing as a political party to ensure that women’s interests are represented throughout the British political landscape. WEP emerged in 2015 out of a dissatisfaction with mainstream politics and a want to put women’s interests at the top of the political agenda. The party reasoned that if women’s equality could be accepted as a ‘vote winner’ by mainstream parties, it would no longer need to exist. WEP leaders boldly called upon mainstream parties to take on its policies and to ‘put it out of business’. This thesis looks at the difficulties WEP has faced in carrying out this rhetorical device in practice. Discourse analysis, interviews, and participatory action research – along with comparisons made with the Feminist Initiative in Sweden, as well as Women’s Alliance/List and Women’s Movement in Iceland – are used to interrogate this important concept. This thesis begins by analysing key aspects of WEP’s identity, including its status as a women’s/feminist party and its non-partisan positioning. It goes on to assess WEP’s abilities to descriptively and substantively represent women, and the party’s unique positioning at the crossroads between movement and institutionalised politics. Ultimately, this thesis looks at how WEP utilises its institutional positioning as a political party, and if permanence is necessary to carry out its aim to represent women. This thesis contributes to broader debates concerning women’s and feminist organising, the development of ‘good representation’ of women, social movements’ interactions with the state, and institutional tools to mobilise effective change. Cambridge Trust Jesus College, Cambridge